(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Religious pilgrimages, such as the Hajj, are widely publicized gatherings that attract millions of people worldwide. These events can strain the public health resources of the host nation, necessitating a high level of readiness and response capacity. This study aims to evaluate the Prevalence of Insomnia and its characteristics among pilgrims during the 2024 Hajj. Materials and Methods: A cross-sectional questionnaire study was conducted over one month in 2024 at the Jeddah International Airport. The questionnaire contained sociodemographic, insomnia, and characteristics, comprising 4 binary-scale items; and (3) awareness of emergency contact numbers for health services and presence of companions in the holy city (2 items). Results: Among the 4,721 pilgrims who responded, 614 (13%) reported insomnia symptoms and met the inclusion criteria for final analysis. The demographic breakdown of these pilgrims showed that 48.2% (n = 296) were male, with 29% (n = 178) aged 31–40 years and 22.8% (n = 140) aged 41–50 years. The most common insomnia symptoms reported were: trouble falling asleep (46.3%), frequent nighttime awakenings (24.4%), difficulty staying awake (10.4%), and feeling unrefreshed after waking up (10.1%). Notably, pilgrims with higher education levels (graduate-level or literate) reported more sleep-related issues, including difficulty staying awake, unrefreshing sleep, frequent awakenings, and snoring. Conclusion: This study reveals that insomnia symptoms exist among pilgrims, with the most frequently reported issues being difficulty initiating sleep, waking up multiple times during the night, struggling to stay awake during the day, and waking up feeling unrested. We recommend educating individuals on the importance of sleep and promoting awareness of sleep health during pre-hajj preparations. In addition, we suggest offering counseling services and support groups for pilgrims who may be experiencing sleep disturbances. These services would focus on stress reduction, relaxation techniques, and coping strategies.